Reframing Undergraduate Economics Education through an Integrated Active and Engaging Learning Model: A Classroom Action Research Study - Dyah Perwita; Retno Widuri; Hana Knollová (Economic Education Analysis Journal, 2026)
This study examines the implementation and effects of the Integrated Active and Engaging Learning Model (IAELM) in undergraduate economics education at a public university in Indonesia, addressing a critical gap where prior studies document active learning benefits but rarely explain how iterative pedagogical refinement improves achievement in lecture-dominated contexts. Using a Classroom Action Research design, the study involved 42 students across three action cycles over one semester, integrating quantitative and qualitative evidence from formative tests, structured observations, and reflective journals. Results show a systematic shift from passive to participatory learning, with mean achievement rising from 62.4 to 81.7, mastery attainment increasing from 38% to 85%, and observable engagement and interaction strengthening across cycles. Performance gains accelerated after instructional stabilization and learner adaptation, suggesting cumulative rather than immediate effects of student-centered learning. The study demonstrates that structured active-engaging pedagogy can measurably improve learning outcomes and participation in economics education, offering a practical model for lecturers seeking to redesign classroom practice while contributing to a clearer process-based understanding of instructional improvement in higher education contexts.